2015
DOI: 10.1200/jco.2014.59.0463
|View full text |Cite
|
Sign up to set email alerts
|

Bias Correction Methods Explain Much of the Variation Seen in Breast Cancer Risks of BRCA1/2 Mutation Carriers

Abstract: Purpose Recommendations for treating patients who carry a BRCA1/2 gene are mainly based on cumulative lifetime risks (CLTRs) of breast cancer determined from retrospective cohorts. These risks vary widely (27% to 88%), and it is important to understand why. We analyzed the effects of methods of risk estimation and bias correction and of population factors on CLTRs in this retrospective clinical cohort of BRCA1/2 carriers. Patients and Methods The following methods to estimate the breast cancer risk of BRCA1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…The high proportion of unaffected mutation carriers in our study seems to reflect an active testing protocol in the Netherlands of at-risk family members of the index patients, who are advised to undergo genetic counseling and DNA testing for the family-specific SDHB mutation. Lower lifetime cancer risks have also been established for other genetic tumor syndromes following the inclusion of unaffected mutation carriers, one well-known example being pathogenic BRCA1/2 gene variants (23). Lower cumulative lifetime risks of breast cancer followed from analyses that excluded index patients while including first-degree relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of unaffected mutation carriers in our study seems to reflect an active testing protocol in the Netherlands of at-risk family members of the index patients, who are advised to undergo genetic counseling and DNA testing for the family-specific SDHB mutation. Lower lifetime cancer risks have also been established for other genetic tumor syndromes following the inclusion of unaffected mutation carriers, one well-known example being pathogenic BRCA1/2 gene variants (23). Lower cumulative lifetime risks of breast cancer followed from analyses that excluded index patients while including first-degree relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The families of the study participants were relatively small (median of two female FDRs), and may not be as informative as larger families. We did not investigate the possible effect of family clustering in our results, however, we do not expect this to have a major impact on the observed associations, as the number of carriers per family was small [6,18].…”
Section: Discussionmentioning
confidence: 88%
“…Up to 24% of OC cases are due to a genetic predisposition, most often associated with BRCA1/2 mutations [2]. Numerous studies aimed at estimating the lifetime OC risk for BRCA1/2 mutation carriers [3][4][5] obtaining varying results according to the population studied and methodology applied [6], with estimates ranging between 31-59% in BRCA1 and 6-18% in BRCA2 mutation carriers [3][4][5]. Subsequent studies aimed to identify genetic and environmental factors associated with the observed risk variation in mutation carriers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Case‐control studies were excluded because sample sizes are too limited to detect rare germline variants in both cases and controls 9 . Study quality was evaluated on common cancer risk estimate variation sources: methodology, patient recruitment, and population characteristics 10 . Overlapping cohorts were included because they provided complementary approaches or outcomes.…”
Section: Methodsmentioning
confidence: 99%